Guidelines for laboratory rearing of insect evidence: the importance of air humidity for breeding of Necrodes littoralis (L.) (Coleoptera: Staphylinidae) - Anna Mądra-Bielewicz; Szymon Matuszewski (Scientific Reports)
Abstract In forensic entomology, effective rearing of insect evidence is crucial as it increases the accuracy of post-mortem interval (PMI) estimation and facilitates species identifications of some evidence. However, virtually no single species has a forensically useful rearing protocol. This study investigates the importance of relative humidity on larval development and fitness of Necrodes littoralis (L.) (Staphylinidae), and proposes an all-inclusive rearing protocol for this forensically important beetle species. We hypothesized that high relative humidity enhances growth, shortens development and promotes thermogenesis. By manipulating relative humidity (50%, 70%, 90%) and the presence of adult beetles during the prelarval phase, we demonstrated that high relative humidity level significantly improved beetle fitness by increasing survival, beetle mass at eclosion and shortening development. Specifically, at 90% relative humidity, beetles showed a twofold increase in mass and a threefold increase in survival compared to 50%. Moreover, thermogenesis was higher at high relative humidity, further facilitating larval growth. These results highlight the key role of humidity for N. littoralis development. Finally, we proposed a comprehensive rearing protocol for N. littoralis to improve forensic investigations involving these beetles and to guide future developments of similar protocols for other insects of forensic importance.